Avanguardie educative, a collaborative network for Italian teachers' professional development - Andrea Nardi; Francesca Pestellini (Je-LKS: Journal of E-Learning and Knowledge Society)
The COVID-19 pandemic posed significant challenges to education, particularly in countries like Italy with limited prior experience in distance learning. To support the educational community during this crisis, a series of 41 webinars was organized, addressing key themes of educational innovation. Rooted in mentoring, knowledge exchange, and reflective practice, this initiative was part of the broader efforts of Avanguardie Educative, a network encompassing nearly 1,600 schools, to adapt to the shift toward remote teaching. Participants completed satisfaction surveys after each webinar and a follow-up questionnaire at the series' conclusion, enabling an analysis of emerging needs in professional development and training. Findings highlighted high levels of satisfaction with the program and confirmed its effectiveness as a tool for coaching and professional growth. The initiative also demonstrated strong networking potential, emphasizing its value in fostering professional learning communities. These results encourage further exploration of how webinar-based technologies can facilitate the exchange of practices and support professional development.